Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Insertion professionnelle dans le domaine de la santé des personnes immigrantes francophones vivant en situation minoritaire - Forest, Mariève; Goss Gilroy Inc (Ministère Immigration, Réfugiés et Citoyenneté Canada, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Occupational Integration in Healthcare by French-speaking Immigrants Living in Minority Communities - Goss Gilroy Inc. (GGI) (2020)
This report presents the results of a research project on the occupational integration of French speaking immigrants in healthcare, in Francophone minority communities. Through interviews, this project examines the challenges faced by French-speaking immigrants working or pursuing a career in the health sector in Nova Scotia, Ontario and Alberta. Researchers also mobilized literature on the occupational integration of immigrants, data from the 2016 Census and the results of quantitative studies. The research shows that the need for English language skills constitutes a major obstacle at various stages of French-speaking immigrants’ occupational integration journey. The interviews also indicate that employment assistance services in French are not equipped to deal with the complex trajectories of internationally educated health professionals, or to help them identify alternative careers. During internships or at the start of employment, supports in French promoting the integration of immigrants (through mentoring, training workshops for employers, etc.) are very limited. Recommendations are addressed to the Department of Immigration, Refugees and Citizenship Canada and aim to improve supports offered to the study population from the start of their migration project to retention in their workplace.

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.